Green markets : the economics of sustainable development - Panaĭotov, Theodore (San Francisco, Calif. : ICS Press, 1993)
Argues that economic growth is not incompatible with protecting the local and global environments. He presents case studies such as forest and land use policy in Brazil, water pricing in China, pesticide policy in Indonesia, and communal resource management in Kenya.
"A copublication of the International Center for Economic Growth and the Harvard Institute for International Development."
Includes bibliographical references (p. 157-162) and index.
oif 16/09/15
Loan
Keywords: Sustainable development -- Developing countries -- Case studies; Environmental policy -- Economic aspects -- Developing countries -- Case studies